The Consciousness and Urdu Ghazal - Saleem Akhtar; Miss Raheela; M.altaf Yousaf zaiee (بازیافت, 2020)
According to psychological study poetry belongs to those dreams of poet that he watches in awaking condition. Freud explains poetry as language of dreams. The atmosphere that we find in Urdu ghazal is approximately similar to all those atmospheres (condition) that is present in human's sub –conscious.